Grinding Uncertainty: Business Model Innovation as a Strategy for Coffee Sector SMEs - Yves Clément Zimmermann (Proceedings, 2023)
The coffee industry, one of the world’s most vital commercial value chains, faces severe challenges, especially among its small- and medium-sized enterprises (SMEs) actors. These challenges encompass social, economic, and environmental crises, with climate change being particularly menacing. This perspective article highlights business model innovation (BMI) as a proactive strategic option for SMEs in the coffee industry, providing a roadmap from the field to the coffee cup for navigating these uncertainties. Drawing on recent BMI research within the coffee sector and related fields, the piece explores transferable strategies and potential implementations, with an emphasis on sustainability-oriented BMI. The discussion identifies both potential benefits and challenges of implementing BMI. Ultimately, the article positions BMI as a promising field for both researchers and practitioners, offering sustainable solutions to the multifaceted challenges faced by the coffee industry.